The Bankruptcy A Novel by Júlia Lopes de Almeida - Suriani da Silva, Ana Claudia (Literature and Translation, 2023)
Set in the early years of the Old Republic after the abolition of slavery, Júlia Lopes de Almeida's The Bankruptcy depicts the rise and fall of a wealthy coffee exporter against a kaleidoscopic background of glamour, poverty, seduction, and financial speculation. The novel introduces readers to a turbulent period in Brazilian history seething with new ideas about democracy, women's emancipation, and the role of religion in society. Originally published in 1901, its prescient critiques of financial capitalism and the patriarchal family remain relevant today. In her lifetime, Júlia Lopes de Almeida was compared to Machado de Assis, the most important Brazilian writer of the nineteenth century. She was also considered for the inaugural list of members of the Brazilian Academy of Letters, but was excluded because of her gender. In the decades after her death, her work was largely forgotten. This publication, a winner of the English PEN award, marks the first novel-length translation of Almeida's writing into English, including an Introduction to the novel and a Translators' preface, and accompanies a general rediscovery of her extraordinary body of work in Brazil.